Partial replacement of high-fat diet with n-3 PUFAs enhanced beef tallow attenuates dyslipidemia and endoplasmic reticulum stress in tunicamycin-injected rats - Zheng, Jiaxiang; Lee, Jisu; Byun, Jaemin; Yu, Daeung; Ha, Jung-Heun (Frontiers in Nutrition, 2023)
Metabolic syndrome (MetS) is considered as a complex, intertwined multiple risk factors that directly increase the risk of various metabolic diseases, especially cardiovascular atherosclerotic diseases and diabetes mellitus type 2. While lifestyle changes, including dietary intervention are effective in mitigating or preventing MetS, there are no specific therapies against MetS. Typical western diets comprise of high saturated fatty acid, cholesterol, and simple sugar; consequently their consumption may increase the potential pathological developmental risk of MetS. Partial replacement of dietary fatty acids with polyunsaturated fatty acids (PUFAs) is widely recommended measure to manage MetS-related disorders. In the present study, we used rat model to investigate the role of n-3 PUFA enriched beef tallows (BT) on MetS and tunicamycin (TM)-induced endoplasmic reticulum (ER) stress, by partially replacing dietary fat (lard) with equal amounts of two different BTs; regular BT or n-3 PUFA-enriched BT. The experimental rats were randomly assigned to three different dietary groups (n=16 per group): (1) high-fat and high-cholesterol diet (HFCD); (2) HFCD partially replaced with regular BT (HFCD+BT1); (3) HFCD partially replaced with n-3 enhanced BT (w/w) (HFCD+BT2). After 10 weeks of dietary intervention, each experimental rodent was intraperitoneally injected with either phosphate-buffered saline or 1 mg/kg body weight of TM. HFCD+BT2 showed improved dyslipidemia before TM injection, and increased serum high-density lipoprotein cholesterol (HDL-C) levels after TM injection. BT replacement groups had significantly reduced hepatic triglyceride (TG) levels, and decreased total cholesterol (TC) and TG levels in epididymal adipose tissue (EAT). Furthermore, BT replacement remarkably attenuated TM-induced unfolded protein responses (UPRs) in liver, showing reduced ER stress, with BT2 being more effective in the EAT. Therefore, our findings suggest that partially replacing dietary fats with n-3 PUFA to lower the ratio of n-6/n-3 PUFAs is beneficial in preventing pathological features of MetS by alleviating HFCD- and/or TM-induced dyslipidemia and ER stress.